Pengaruh Penerapan Faktur Pajak Elektronik (E-Faktur) Terhadap Kepatuhan Wajib Pajak Untuk Pelaporan SPT Masa PPN Pada KPP Pratama Bandung Cibeunying - Riri Rumaizha; Asep Supriatna (LPPM POLITEKNIK LP3I BANDUNG, 2022)
This project aims to see The Effect of Electronic Tax Invoice (e- Invoice) on Taxpayer Compliance in Reporting VAT Periodic Tax Return at Cibeunying Regional Tax Office. The independent variable used is electronic tax invoice while the dependent variable is taxpayers compliance in reporting VAT Periodic Tax Return. The population in this project were taxable entreprenuers which registered in Cibeunying Regional Tax Office, whom using e-Invoice by number of sample are 50 taxable entrepreneurs. Data collection technique are performed by literature studies and questionnaires, while SPSS used for the data analyses technique. This project conclude the result that the electronic tax invoice (e-invoice) has positively and significantly effected taxpayer compliance in reporting VAT Periodic Tax Return at Cibeunying Regional Tax Office.